Study of Gender Preferences for Locations Around the World Using Social Media Data - Müller, Willi; Silva, Thiago H; Almeida, Jussara M; Loureiro, Antonio A F (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2016: Proceedings of the 22nd Brazilian Symposium on Multimedia and the Web, 2016)
Traditional methods for obtaining data to conduct gender studies may be cumbersome because, usually, data are obtained manually through questionnaires. However, this poses challenges in conducting such studies on a large scale. Thus, available studies using traditional methods often provide analysis only at country level. In this paper, we explore the use of check-ins data collected from Foursquare to estimate the cultural gender preferences for locations in the physical world. Our results suggest that gender preferences can be captured for locations at different spatial granularity – not just for countries. This indicates that our proposed methodology could inspire a complementary approach to conduct studies of gender preferences for locations.